Blood-Brain Barrier Permeable Chitosan Oligosaccharides Interfere with β-Amyloid Aggregation and Alleviate β-Amyloid Protein Mediated Neurotoxicity and Neuroinflammation in a Dose- and Degree of Polymerization-Dependent Manner - Zhu, Limeng (Mar Drugs, 2020)
It is proven that β-amyloid (Aβ) aggregates containing cross-β-sheet structures led to oxidative stress, neuroinflammation, and neuronal loss via multiple pathways. Therefore, reduction of Aβ neurotoxicity via inhibiting aggregation of Aβ or dissociating toxic Aβ aggregates into nontoxic forms might be effective therapeutic methods for Alzheimer’s disease (AD) treatment. This study was designed to explore interference of chitosan oligosaccharides (COS) on β-(1-42)-amyloid protein (Aβ42) aggregation and Aβ42-induced cytotoxicity. Here it was demonstrated that COS showed good blood-brain barrier (BBB) penetration ability in vitro and in vivo. The experimental results showed that COS efficiently interfered with Aβ42 aggregation in dose- and degree of polymerization (DP)-dependent manners, and COS monomer with DP6 showed the best effect on preventing conformational transition into β-sheet-rich structures. Based on the binding affinity analysis by microscale thermophoresis (MST), it was confirmed that COS could directly bind with Aβ42 in a DP-dependent manner. Our findings demonstrated that different performance of COS monomers with different DPs against Aβ42 assembly was, to some extent, attributable to their different binding capacities with Aβ42. As a result, COS significantly ameliorated Aβ42-induced cytotoxicity. Taken together, our studies would point towards a potential role of COS in treatment of AD.